FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI USAHA TANI JAGUNG DI KECAMATAN JEROWARU KABUPATEN LOMBOK TIMUR: FACTORS AFFECTING CORN FARMING PRODUCTION IN JEROWARU DISTRICT, EAST LOMBOK REGENCY - nanang hermawan (Journal of Agri Rinjani: Social Agricultural Economics - Faculty of Agriculture, UGR, 2024)
The varying altitude of the region causes the production of the agricultural sector in East Lombok Regency to be quite diverse. In addition, in East Lombok Regency there is Mount Rinjani. Volcanic ash from this volcano can fertilise the soil around the mountain, causing East Lombok Regency to have the potential to develop food crops. Some areas away from the mountains include dry land that is suitable for food crops, especially corn, which has potential in East Lombok Regency. This study aims to find out the costs and income along with the factors that influence corn production in Jerowaru sub-district. This research is descriptive research. The technique of taking respondents using Quota Sampling with Proportional Random Sampling technique so that 30 respondents were obtained. The data collection technique is by means of a survey by going directly to the field. Analysis of research data using Cobb-Douglas. The results showed that the factors affecting the production of corn farming in Jerowaru Subdistrict, namely land area, fertilizer, and seeds have a real and significant effect on corn production in Jerowaru Subdistrict while pesticides and labour do not significantly affect production.   Keywords: Farming, Production Value, Income